The Development of Modules Based on Spiritual in Viruses Topic For Senior High School Students - Dina Ristiana Anesa; Ardi Ardi (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
The purpose of this research is develop a module of spiritual nuance on viruses material for students SMA/MA valid and practical. This research uses 3 of 4 stages 4D models that is define, design, and develop. The developed product was validated by 4 validators including 3 lecturers of biology and 1 biology teacher of SMAN 12 Padang, while for practicality will be done by 33 students of SMAN 12 Padang. The data of this study include the primary data obtained from the questionnaire filled directly by the subject of research. Based on the result of the study obtained the validity of 3,61 with very valid criteria, practicality by teachers 3,49 with very practical criteria and practicality by students 3,38 with very practical criteria.